Modern Sanskrit Translations of Omar Khayyam’s Rubaiyats: Navigating Cultural and Linguistic Landscapes - Karcz, Marta (Folia Orientalia, 2025)
This article explores two modern Sanskrit translations of Omar Khayyam’s Rubaiyats, created independently by Pandit Adibhatla Narayana Das (1937) and Professor Narahari Govind Suru (1981). Both scholars worked from Edward FitzGerald’s English version, adapting it into Sanskrit according to classical poetic conventions. Through a comparative analysis, the study examines the translators’ differing choices of metre, diction, and cultural adaptation, highlighting how each negotiates the challenges of rendering Khayyam’s philosophical quatrains within the rigid structure and aesthetic expectations of Sanskrit poetry. Attention is also given to strategies of domestication and foreignisation, revealing how each translator reinterprets the Persian original within an Indian literary and intellectual context. Ultimately, these translations not only exemplify creative engagement with classical Sanskrit forms but also illuminate broader processes of cross-cultural mediation and the modern reinvention of Sanskrit literary expression.